Filamentation of Campylobacter - Ghaffer, Nacheervan M. (2016)
The bacterial pathogen Campylobacter jejuni is a leading cause of foodborne gastroenteritis worldwide. Consumption of contaminated poultry meat is considered a major source of infection. Changes in cell morphology were demonstrated to occur spontaneously on entry in to stationary phase, with development of filamentous cells amongst short spiral morphotypes. The aim of this study was to investigate differences between the morphotypes of C. jejuni and C. coli and gain insights into their development. Using a minimal culture medium filament formation was observed to be wide spread amongst C. jejuni strains tested but was not universal in C. coli strains. Filamentation did not appear to arise due to the release of diffusible molecules or the accumulation of either toxic metabolites or oxidative stressors in the medium. Separated filaments exhibited greater intracellular ATP contents compared to spiral cells, and were able to survive longer in water at 4 and 37 C. C. jejuni 12661 was identified as producing long filaments but genome sequence analysis provided no clear explanation for the enhanced filament formation. Using RNA-Seq, transcriptome differences were examined between cells growing in exponential phase and separated cell morphotypes recovered from stationary phase cultures of the C. jejuni strains 12661 and PT14. These studies identified profound transcriptional differences between the cell morphotypes present at stationary phase, and highlighted problems of interpreting such data without separation of these sub-populations. Stationary phase cells of either morphotype were impaired in motility, which likely resulted from down-regulation of rpoN encoding sigma factor 54, and several key motility associated genes. The spoT gene of C. jejuni mediates the synthesis of ppp(G)pp as part of the stringent response to stress. The spoT gene was differentially regulated in the stationary phase morphotypes recovered in this study, as were the genes encoding the phosphohydrolases PPX1/PPX2 and polyphosphate kinases PPK1/PPK2 that control cellular (p) pp(G)pp pools. Prominent heat-shock and oxidative stress responses were evident in stationary phase cells compared to cells in exponential growth phase but transcription of the ribosomal proteins was not down-shifted. The transcript levels of several cell division associated genes were down-regulated in stationary phase spiral and filamentous cells. The formation of long filamentous cell morphotypes by C. jejuni 12661 corresponds with reduced expression of maf (inhibitor of septum formation), mreB (actin-like rod-shape determining protein), mreC (rod-shape determining protein), parA, parB (chromosome partitioning proteins), ftsA (actin-like function in cytokinesis), ftsH (ATP-dependent zinc metallopeptidase), ftsW (lipid II-linked peptidoglycan transporter) and ftsZ (tubulin-like z-ring formation) that collectively function in septum formation between daughter cells.